Estrategias para el proceso de reciclaje de desechos tecnológicos en el cantón Durán con miras a generar fuentes de empleo para los recicladores informales del sector y disminuir los niveles de contaminación ambiental - Alejandro Rosado, Violeta (2013)
This research work entitled "Strategies for the process e-waste recycling in the Canton Durán in order to generate employment opportunities for informal sector recyclers and lower levels of environmental pollution" is a response to the needs that the people living in this county, as a result of environmental pollution that is generated there, due to the inadequate management of technology is discarded without any classification or contingency average. In this context, the work has been divided into five chapters which are briefly described below: 1. Chapter I, there will be an explanation of the problem situation manifested in Canton Durán, specifically in terms of environmental pollution and recycling levels to justify the development of this work and set objectives that start up a proposal should be met……